The Inverse Epsilon Distribution as an Alternative to Inverse Exponential Distribution with a Survival Times Data Example - Jónás, Tamás; Chesneau, Christophe; Dombi, József; Bakouch, Hassan Salah (Acta Cybernetica, 2022)
This paper is devoted to a new flexible two-parameter lower-truncated distribution, which is based on the inversion of the so-called epsilon distribution. It is called the inverse epsilon distribution. In some senses, it can be viewed as an alternative to the inverse exponential distribution, which has many applications in reliability theory and biology. Diverse properties of the new lower-truncated distribution are derived including relations with existing distributions, hazard and reliability functions, survival and reverse hazard rate functions, stochastic ordering, quantile function with related skewness and kurtosis measures, and moments. A demonstrative survival times data example is used to show the applicability of the new model.